Lost - Ikon Gallery, Birmingham; Kovats, Tania; Rogoff, Irit; Watkins, Jonathan; Exhibition. Lost. Ikon Gallery Birmingham. 2000-02-16. 2000-04-02 (Birmingham : Ikon Gallery, 2000)
Bourgeois, Louise ; Celmins, Vija ; de Cordier, Thierry ; Evans, Cerith Wyn ; Gonzalez-Torres, Felix ; Horn, Roni ; Kahlhamer, Brad ; Kippenberger, Martin ; Kovats, Tania ; Le Corbusier ; Martin, Agnes ; McCarthy, Paul ; Opie, Julian ; Patterson, Iain ; Shine, Vincent ; Tillmans, Wolfgang
Lost, Ikon Gallery, Birmingham, 16 February - 2 April 2000
Engels
boek